Bio-functional enhancement of plant based-haemagglutinin by fusion with IgMFc - Van, Pham Thi; Hoang, Phan Trong; Thuong, Ho Thi; Thu Giang, Nguyen; Ngoc, Pham Bich; Trang, Vu Huyen; Conrad, Udo; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2020)
The creation of recombinant oligomeric haemagglutinin proteins from A/H5N1 virus is a new concern for many scientists. In this study, the gene encoding the haemagglutinin protein (H5TG) derived from virus A/duck/Vietnam/TG24-01/2005 was fused with three different motifs (GCN4pII, GCN4pII-IgMFc and GCN4pII-ELP-IgMFc) in order to form three recombinant proteins (trimeric H5TGpII, oligomeric H5TGpII-IgMFc and ELPylated oligomeric H5TGpII-ELP-IgMFc, respectively) for enhancing protein expression, bio-function and purification of H5TG. These H5TG fragments have been attached to expression cassettes in the pCB301 shuttle vector, transiently expressed in Nicotiana benthamiana by agroinfiltration, then the protein expression was confirmed by SDS-PAGE and Western blot analysis. The results showed that the expression level of the H5TGpII-ELP-IgMFc protein in plant raw extract was stronger than that of two other proteins analyzed in this paper. Evaluation of bio-function showed that the haemagglutination titre (HA titre) of the total solution protein extract containing H5TGpII-IgMFc protein was highest (64 HAU) compared to that containing two remaining proteins (8 HAU). Subsequently, the H5TGpII and H5TGpII-IgMFc proteins were purified by immobilized metal ion affinity chromatography (IMAC), while the H5TGpII-ELP-IgMFc protein was purified using membrane-based Inverse Transition Cycling (mITC). The oligomer state of the purified proteins was then determined by non-reducing SDS-PAGE. The haemagglutination assay analysis of purified proteins showed that the lowest protein amount causing erythrocyte agglutination (1 HAU) of the H5TGpII-IgMFc protein was 0.06 µg and lower four times than that of H5TGpII and H5TGpII-ELP-IgMFc proteins (both of them were 0.24 µg). This indicates that the fusing of the GCN4pII-IgMFc motif into the H5TG protein gives the stronger bio-function than the fusing of two remaining motifs into this protein. This result opens up the applicability of the IgMFc for generation of oligomer proteins to enhance the bio-function of target proteins in the study of recombinant vaccine production.